Association of periodontitis, tooth loss, and self-rated oral health with circadian syndrome in US adults: a cross-sectional population study - Yibo Li; Yuhao Liu; Tao Yin; Mi He; Changyun Fang; Xiong Tang; Shifang Peng; Yundong Liu (BMC Oral Health)
Abstract Background This study was to investigate associations of periodontitis, tooth loss and self-rated oral health with circadian syndrome. Methods Data regarding periodontitis, dentition, oral health questionnaire and circadian syndrome of 30–85 years old participants from US National Health and Nutrition Examination Survey 2005–2020 were analyzed. Periodontitis questions for periodontitis and dentition status were validated. Weighted multivariable logistic regression analyses were used. Results Weighted prevalence of circadian syndrome and stage II-IV periodontitis was 33.29% and 88.87%, respectively. When compared with stage I periodontitis, stage II periodontitis was significantly associated with greater circadian syndrome prevalence after adjustment (odds ratio (OR) and 95% confidence interval (CI): Stage II: 1.35 (1.03, 1.76), P = 0.032; Stage III: 1.30 (0.97, 1.73), P = 0.069; Stage IV: 1.17 (0.82, 1.65), P = 0300). Stage II periodontitis was significantly associated with greater prevalence of lower high-density lipoprotein cholesterol (HDL) and elevated triglycerides and stage III and stage IV periodontitis were significantly associated with greater hypertension prevalence. A 1 tooth increase in the number of missing teeth was associated with a 1% increase in circadian syndrome and its components of obesity, elevated fasting plasma glucose (FPG) and short sleep. Poor or fair self-rated oral health showed a specificity of > 70% for periodontitis and lack of functional dentition. Meanwhile, poor or fair self-rated oral health had relatively higher levels of sensitivity for stage II-IV periodontitis (35%), stage III-IV periodontitis (46%), stage IV periodontitis (60%) and lacking functional dentition (56%). When compared to excellent self-rated oral health, good, fair and poor self-rated oral health were significantly associated with higher circadian syndrome prevalence (OR and 95% CI: Very good: 1.13 (0.97, 1.32), P = 0.120; Good: 1.34 (1.14, 1.57), P < 0.001; Fair: 1.41 (1.16, 1.71), P = 0.001; Poor: 1.63 (1.32, 2.03), P < 0.001). Additionally, participants with worse self-rated oral health had significantly higher prevalence of elevated FPG, hypertension, low HDL, elevated triglycerides, short sleep and depression. Conclusions Periodontitis, tooth loss and worse self-rated oral health were associated with circadian syndrome in US adults. Self-rated oral health may be a simple question to indicate oral and systemic health.